Application of the NHT Model Combined with Question Cards on Biology Learning Outcomes - Nurjannah, Nabilla Riska; Djumadi, D (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Online learning that lasts more than two years makes it difficult for teachers to measure learning outcomes in the attitude and psychomotor aspects of students. Students tend to be silent and passive which makes learning difficult to be interactive. Teachers need to apply learning innovation strategies so that students are more enthusiastic in learning. This study aims to determine the learning outcomes of class XI MIPA students at SMA Negeri 5 Surakarta in the 2022/2023 school year on the subject of the human reproductive system by applying the Numbered Head Together (NHT) learning model combined with question cards. This study used a quantitative approach with a quasi-experimental method involving two classes, namely class XI MIPA 1 as the experimental class and class XI MIPA 4 as the control class, each of which consisted of 36 students. The instruments used in this study were multiple choice question sheets to determine students' cognitive learning outcomes and observation sheets to determine student activity. The posttest average score for the cognitive aspects of the control class was 78.5 and that of the experimental class was 87.72. Meanwhile, the average percentage of student activity (PKS) for the affective aspect of the control class was 71.14% and that of the experimental class was 82.27%. The data analysis technique uses the Independent Sample T-Test, which was previously tested for normality and homogeneity. The results of the F test show that there is a difference in the average values in the two classes (sig. 0.000 <0.05). The application of NHT is able to increase student activity in class.